[3 Travel Maps] - Belcher, Edward, Sir (L. Reeve, 1855)
Three travel maps which are meant to accompany a text about expeditions in the area. The first map shows the north pole and northernmost parts of North America and Greenland; some exploration routes and geographic features are noted. The second map shows exploration and discoveries in the Arctic Sea area with regions and some geographic features noted. The third map is a nautical chart of the Port of Lievely with depths marked in fathoms and some relief of surrounding land marked.